Hábitos bucales deformantes y su relación con las maloclusiones dentarias - Armijos Saca., María del Rosario (2022)
Deforming oral habits are one of the main factors that contribute to the appearance of dental malocclusions that significantly influence the quality of life of people, emerging not only its functional aspect but also its psychological and aesthetic aspect. , Oral habits at an early age begin to present abnormalities in anterior occlusion but need to prevail longer or be more intense to cause subsequent malocclusions. The objective of this bibliographical review is to determine the relationship between deforming oral habits and dental malocclusions; likewise its causes, consequences and most ideal treatment in children from 4 to 12 years old. Also, determine the most frequent oral habits that lead to dental malocclusions. For the preparation of this bibliographic review, the collection of scientific articles between the years 2012-2022 was carried out, whose universe was made up of 100 scientific articles of which, according to the inclusion criteria, 40 articles were taken as a sample to be analyzed. . After the analysis of the information, it was obtained as a result that there is a relationship between deforming oral habits and the development of dental malocclusions. Likewise, the most frequent deforming oral habits are finger sucking (40%), onychophagia (30%), atypical swallowing (20%), and oral breathing (10%). In the same way, it was obtained as a result that deforming oral habits produce anterior open bite and posterior crossbite in 80%; in 40% Angle class II malocclusion, and in 10% dental crowding and dental malposition. Malocclusions such as anterior open bite, posterior crossbite, and Angle class II malocclusion were related to the habit of finger sucking, atypical swallowing, and oral breathing. While crowding and dental malposition were related to onychophagy Keywords: Finger sucking, oral breathing, onychophagia, open bite.